2004
DOI: 10.1016/j.ydbio.2004.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-2 can mediate myocardial regulation of atrioventricular cushion mesenchymal cell formation in mice

Abstract: Transformation of endocardial endothelial cells into invasive mesenchyme is a critical antecedent of cardiac cushion tissue formation. The message for bone morphogenetic protein (BMP)-2 is known to be expressed in myocardial cells in a manner consistent with the segmental pattern of cushion formation [Development 109(1990) 833]. In the present work, we localized BMP-2 protein in atrioventricular (AV) myocardium in mice at embryonic day (ED) 8.5 (12 somite stage) before the onset of AV mesenchymal cell formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
177
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(187 citation statements)
references
References 52 publications
8
177
1
1
Order By: Relevance
“…BMP-2 is expressed in the embryonic aorta (46), and is known to be involved in interactions between ectodermal and mesodermal cells during development (47,48). Furthermore, it has a role in EC differentiation; BMP-binding endothelial cell precursor-derived regulator, a recently described BMP antagonist in EC, inhibits both BMP signaling and EC differentiation (49).…”
Section: Discussionmentioning
confidence: 99%
“…BMP-2 is expressed in the embryonic aorta (46), and is known to be involved in interactions between ectodermal and mesodermal cells during development (47,48). Furthermore, it has a role in EC differentiation; BMP-binding endothelial cell precursor-derived regulator, a recently described BMP antagonist in EC, inhibits both BMP signaling and EC differentiation (49).…”
Section: Discussionmentioning
confidence: 99%
“…BMP and FGF signaling pathways have previously been shown to be important for normal heart development including endocardial cushion formation, cushion elongation, and remodeling (Galvin et al, 2000;Gaussin et al, 2002;Delot et al, 2003;Jiao et al, 2003;Sugi et al, 2003Sugi et al, , 2004Somi et al, 2004;Ma et al, 2005;Lincoln et al, 2006a). A number of BMP ligands have been identified in the developing heart; in particular, BMP4 is expressed in the OFT myocardium adjacent to the endocardial cushions during early stages of valve development (Keyes et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although explants normally require AVC myocardium for EMT to take place, BMP2 induces EMT in mouse AVC explants without AVC myocardium. Moreover, noggin, a BMP antagonist, blocks EMT [50] and addition of BMP2 to ventricular explants (normally unable to undergo EMT) induces EMT [51]. These together indicate that BMP2 is a critical factor required for EMT and initial formation of the cardiac cushions.…”
Section: Bmp Signalling In Cardiac Valve Developmentmentioning
confidence: 93%
“…At E9.5, a heart tube is identifiable in BMP2 −/− embryos but chambers are indistinguishable and thus precludes examination of BMP2 in cardiac cushion formation [49]. Given that BMP2 is highly expressed in the AVC myocardium prior to valve formation [50], Ma et al deleted BMP2 specifically in the myocardium using Nkx2.5-Cre [39] and demonstrated that BMP2 is required for formation of cardiac jelly and for initiation and formation of the cardiac cushions [39]. Additionally, although explants normally require AVC myocardium for EMT to take place, BMP2 induces EMT in mouse AVC explants without AVC myocardium.…”
Section: Bmp Signalling In Cardiac Valve Developmentmentioning
confidence: 99%
See 1 more Smart Citation